2011
DOI: 10.1039/c0dt01105c
|View full text |Cite
|
Sign up to set email alerts
|

Coulombic inter-ligand repulsion effects on the Pt(ii) coordination chemistry of oligocationic, ammonium-functionalized triarylphosphines

Abstract: The Pt(II) coordination chemistry of oligocationic ammoniomethyl- and neutral aminomethyl-substituted triarylphosphines (L) is described. Complexes of the type PtX(2)(L)(2) (X = Cl, I) have been isolated and characterized. For the hexa-meta-ammoniomethyl-substituted ligands [1](6+) and [2](6+), two ligands always occupy a trans-configuration with respect to each other in complexes of the type PtX(2)(L)(2), while for the tri-para-ammoniomethyl-substituted ligand [7](3+), the trans/cis ratio is dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…For PtI 2 {PPh 2 (C 6 H 4 -p-SO 3 K)} 2 with KI, the trans/cis ratio considerably changed from 6/5 to 3/7. These results are consistent with the recent report that the trans/cis ratio decreases with increasing the ionic strength of solution [49]. Thus the observed results for the stereoisomeric ratio may be attributed to a strong intramolecular interligand Coulombic repulsion between the ionic phosphine ligands, which disfavors the cis-isomer.…”
Section: Stereoisomerism Of MX 2 Lsupporting
confidence: 94%
See 1 more Smart Citation
“…For PtI 2 {PPh 2 (C 6 H 4 -p-SO 3 K)} 2 with KI, the trans/cis ratio considerably changed from 6/5 to 3/7. These results are consistent with the recent report that the trans/cis ratio decreases with increasing the ionic strength of solution [49]. Thus the observed results for the stereoisomeric ratio may be attributed to a strong intramolecular interligand Coulombic repulsion between the ionic phosphine ligands, which disfavors the cis-isomer.…”
Section: Stereoisomerism Of MX 2 Lsupporting
confidence: 94%
“…Since intramolecular interligand Coulombic repulsion is diminished at higher ionic strengths due to shielding of the charges [41,49], further experiments on the stereoisomers were performed in potassium halide solution of DMSO. Treatment of DMSO-d 6 solution of PdCl 2 {PPh 2 (C 6 H 4 -p-SO 3 K)} 2 (the trans/cis ¼ ca.…”
Section: Stereoisomerism Of MX 2 Lmentioning
confidence: 99%
“…[28] In addition, several halometallates exhibit halogen-halogen contacts in the solid state either by self-association or by coordination to (poly)halides. [29] These contacts are typically very weak, however, and it is unclear whether they should be characterized as XB. [30] Polyhalides 2À ,w hich form linear XB adducts in crystal structures if the terminal halides are coordinated by further interactions,m ay also feature AEXBs.…”
Section: Introductionmentioning
confidence: 99%
“…It was thus concluded that the intramolecular, interA C H T U N G T R E N N U N G liA C H T U N G T R E N N U N G gand Coulombic repulsion disfavors the cis isomer and is attenuated at higher ionic strengths due to shielding of the charges. [113] Through further measurements of the trans/cis equilibrium position at different temperatures, the thermodynamic parameters for trans-cis isomerization were determined at À22.0 kJ mol À1 for [NaI] = 0.0 m and À32.3 kJ mol À1 for [NaI] = 0.2 m. Thus, trans-cis conversion results in a significantly larger negative enthalpy change in the presence of 0.2 m NaI, confirming the stabilization of the cis isomer by the added NaI.…”
mentioning
confidence: 97%
“…In contrast, sterically similar, neutral aminomethyl-substituted analogues of these ligands lead to formation of the corresponding cis complexes. [113] In the case of complex [PtI 2 (11) 2 ] (Scheme 10), a mixture of cis and trans stereoisomers was obtained. Importantly, the trans/cis ratio was found to be dependent on the ionic strength of the solution, with a higher ionic strength leading to a lower trans/cis ratio (Figure 1).…”
mentioning
confidence: 98%